Correlation between anticoagulant initiation time and thrombolysis at 30 days after anticoagulation therapy in patients with pulmonary embolism - Zhou, Yaojie; Yang, Danrong; Liu, Yi (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to investigate the correlation between anticoagulant initiation time and thrombolysis at 30 days after anticoagulation therapy in patients with pulmonary embolism (PE).MethodsPatients with PE who were hospitalized in the Department of Respiratory Medicine were enrolled. Based on computed tomography pulmonary angiography (CTPA) performed 30 days after anticoagulation therapy, patients were categorized into the complete thrombolysis group (n = 112) and the incomplete thrombolysis group (n = 93). A retrospective analysis was conducted on risk factors, clinical characteristics, and auxiliary examinations. Spearman's correlation analysis was used to assess the association between anticoagulant initiation time and thrombolysis at 30 days. Receiver operating characteristic (ROC) curve analysis was applied to determine the optimal cut-off point for anticoagulation initiation time in PE.ResultsThe proportion of patients with complete thrombolysis at 30 days was 54.63% (112 of 205). Spearman's correlation analysis indicated a significant negative correlation between anticoagulant initiation time and thrombolysis at 30 days (Rs = −0.411, P < 0.001). ROC curve analysis showed that anticoagulant initiation time predicted thrombolysis at 30 days (AUC: 0.736, 95% CI: 0.668–0.804, P < 0.001). The Youden index was 0.071, and the optimal cut-off point for anticoagulant initiation time was <6.5 days, which was associated with the best therapeutic effect.ConclusionAnticoagulant initiation time, PAOI, DVT, and malignant tumors were negatively correlated with thrombolysis at 30 days after anticoagulation therapy. Thrombus absorption within 1 month was significantly improved when anticoagulant therapy was initiated within 6.5 days.